2021
DOI: 10.3390/nu13061760
|View full text |Cite
|
Sign up to set email alerts
|

Calcifediol Treatment and Hospital Mortality Due to COVID-19: A Cohort Study

Abstract: Context. Calcifediol has been proposed as a potential treatment for COVID-19 patients. Objective: To compare the administration or not of oral calcifediol on mortality risk of patients hospitalized because of COVID-19. Design: Retrospective, multicenter, open, non-randomized cohort study. Settings: Hospitalized care. Patients: Patients with laboratory-confirmed COVID-19 between 5 February and 5 May 2020 in five hospitals in the South of Spain. Intervention: Patients received calcifediol (25-hydroxyvitamin D3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 65 publications
6
88
1
3
Order By: Relevance
“…After a scrupulous literature search and a meticulous study selection process, we included 13 studies in the present meta-analysis [7][8][9][10][11][12][13][14][15][22][23][24][25], pooling data retrieved from 2933 patients with COVID-19 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a scrupulous literature search and a meticulous study selection process, we included 13 studies in the present meta-analysis [7][8][9][10][11][12][13][14][15][22][23][24][25], pooling data retrieved from 2933 patients with COVID-19 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies catered to the use of vitamin D before the diagnosis of COVID-19 [9,12,14,23,24], while seven studies had reported the use of vitamin D after the diagnosis of COVID-19 [7,10,11,13,15,22,25]. Annweiler et al [8] had considered the use of oral cholecalciferol in the week following the suspicion or diagnosis of COVID-19 or during the previous month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis indicates that low levels of vitamin D (20–30 ng/mL) are associated with a greater susceptibility to SARS-CoV-2 infection, as well as severity and mortality of COVID-19 [ 62 ]. Conversely, in a multicenter retrospective study, supplemental 25-OHD during the first month of hospitalization reduced in-hospital mortality [ 63 ]. Thus, it is not surprising that vitamin D has been touted as a potential therapeutic adjunct to conventional approaches in the treatment of COVID-19 [ 56 , 57 , 60 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the PubMed database was mined for vitamin D/VDR data relevant to the aberrant immune response of COVID-19 and yielded the following. Studies addressing the prophylactic or therapeutic efficacy of vitamin D for the ARDS of COVID-19 are limited [ 57 , 63 , 65 , 66 , 67 ]. A transgenic murine model of COVID-19 that mimics the disease in humans is available [ 68 , 69 ]; however, it has not been used for interventional studies of vitamin D/VDR signaling.…”
Section: Introductionmentioning
confidence: 99%